Challenges in application of German higher vocational education mechanism in Chinese School-enterprises - Li-Hong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research study examined the historical development, implementation institutions, teaching models, and other aspects of German higher vocational education (HVE) in relation to the adoption of School-enterprise (S-E) cooperation in the Chinese HVE. The evidence was collected through feedback, evaluation indexes, and weights of the effectiveness of the “dual system” that is the backbone of S-E collaboration in vocational education. In order to test the practicability, reliability, stability, and operability of the evaluation model, for the feasibility of research, the “dual-system” of S-E cooperation in the Chinese higher vocational colleges was selected as the subject of this research. The objective was to test the effectiveness of the S-E cooperation in vocational education running in China. A comprehensive evaluation index system for the point of S-E cooperation in vocational education in China was constructed. It was supported by the fuzzy evaluation method of S-E collaboration in Chinese vocational education. The scale collected self-evaluation data and used the fuzzy comprehensive evaluation model to measure the extent of the S-E cooperation in China's vocational education. It was evident due to the varying differences between Germany and China. It was too difficult to adopt the German model of S-E cooperation in the Chinese vocational school unless an innovative approach was adopted. The study recommends adopting innovative measures and customizing the HVE programs in accordance with the Chinese socio-cultural practices and individual requirements of individual students.